2014
DOI: 10.1590/s0100-204x2014000400008
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and nitrogen fixation efficiency of rhizobia isolated from nodules of Centrolobium paraense

Abstract: The objective of this work was to isolate and characterize rhizobia from nodules of Centrolobium paraense and to evaluate their symbiotic efficiency. Soil samples collected from four sites of the Roraima Cerrado, Brazil, were used to cultivate C. paraense in order to obtain nodules. Isolates (178) were obtained from 334 nodules after cultivation on medium 79. Twenty-five isolates belonging to six morphological groups were authenticated using Vigna unguiculata and they were characterized by 16S rRNA. Isolates i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…Recent studies on phenotypic characteristics of isolates from tropical arboreal legumes have shown the existence of nodulating bacteria with characteristics that are compatible with those of the Rhizobium and Bradyrhizobium genera and equivalent frequencies between these phenotypic groups were observed (Gehlot et al, 2012), i.e., the predominance of fast growth bacteria which, acidify the medium pH (Freitas et al, 2014) or the predominance of slow growth bacteria with an alkaline reaction in the culture medium (Baraúna et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies on phenotypic characteristics of isolates from tropical arboreal legumes have shown the existence of nodulating bacteria with characteristics that are compatible with those of the Rhizobium and Bradyrhizobium genera and equivalent frequencies between these phenotypic groups were observed (Gehlot et al, 2012), i.e., the predominance of fast growth bacteria which, acidify the medium pH (Freitas et al, 2014) or the predominance of slow growth bacteria with an alkaline reaction in the culture medium (Baraúna et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Centrolobium paraense is capable of forming nodules with rhizobia native to the soil of Amazonia (Souza et al , 1994; Baraúna et al ., 2014), and bacteria belonging to the genera Bradyrhizobium and Rhizobium have been reported as symbionts of Centrolobium species. However, previous studies have not identified these bacteria at the species level (Moreira et al , 1998; Pagano, 2008; Baraúna et al ., 2014).…”
mentioning
confidence: 99%
“…A recent investigation of the ecology of root-nodulating bacteria isolated from Centrolobium paraense grown in soils collected from different areas in Roraima State, Brazil, found that about 90 % of the 178 isolates exhibited phenotypic characteristics similar to species of the genus Bradyrhizobium (Baraúna et al , 2014). Analysis of partial 16S rRNA gene sequences confirmed these results, but placed these isolates in branches different from previously described species.…”
mentioning
confidence: 99%
“…Strains (BR 10245 T , BR 10290, BR 10351, BR 10346, BR 10303 T , BR 10362, BR 10365, BR 10355, BR 10363, BR 10356, BR 10358, BR 10348, and BR 10359) were cultured on YMA medium at 28 °C, lyophilized and maintained at −80 °C for long-term storage. All strains originally isolated by Baraúna et al (2014) were deposited in Johanna Döbereiner Biological Resources Center-CRB-JD-Embrapa Agrobiologia, Rio de Janeiro, Brazil (http:// www.embrapa.br). The strains BR 10245 T and BR 10303 T were also deposited at the Hambi Culture Collection, Helsinki, Finland (http://www.helsink.fi/hambi) as HAMBI 3597 T and HAMBI 3602 T , respectively.…”
Section: Strains Morphology and Phenotypic Characterizationmentioning
confidence: 99%
“…Continued polyphasic analysis of the Bradyrhizobium strains previously isolated from Centrolobium paraense revealed two new groups with distinct phylogenetic positions from the currently described species (Baraúna et al 2014). In this study, 13 strains were investigated in detail using gene sequence analysis (16S rRNA,dnaK,glnII,recA,rpoB,nodC,and nifH) and Average Nucleotide Identity (ANI).…”
Section: Introductionmentioning
confidence: 98%